Annual Statistical Abstract for Tamil Nadu 1993-94 - Planning Commission (Planning Commission, 1993)
Population Growth , Index Numbers of Agricultural Economy , Index Number of Industrial Production , Index Number of Wholesale Price , Consumer Price Index Number For Industrial Workers. , Consumer Price Index Number For Urban Non-Manual Employees , All India Average Consumer Price Index Number For Industrial Workers , Consumer Price Index Number For Rural Tamil Nadu , Consumer Price Index Number For Urban Tamil Nadu , Index Number of Total Value of Foreign Export and Import
Annual Statistical Abstract for Tamil Nadu 1993-94
Government of Tamil Nadu